Career Choice and the Strength of Weak Ties - Semih Tumen (Institute of Labor Economics (IZA), 2016)
This paper argues that the structure (i.e., size and composition) of the informal search network is a crucial determinant of the career decisions of young workers. Building on the search-theoretic career choice and job mobility model proposed by Neal (1999), I compare the consequences of career advice by one's weak ties versus that by strong ties. The main result is that receiving help from weak ties is associated with early career and job settlements, while the strong ties are more likely to lead to amplified mobility and generate mismatch. Given a network size, I find a strongly positive correlation between the fraction of weak ties among one's informal connections and the likelihood of settling on a stable career path early in the life course. I also find that the sign of this correlation persists, while the magnitude gets smaller as the network size increases. I conclude that the strength-of-weak-ties hypothesis can shed light on the complexity of job mobility patterns among young workers. The model can explain why it takes much longer for blacks – whose informal networks are documented to consist of strong ties – to locate a stable career path than their white counterparts. It also predicts that young workers from closed and segregated neighborhoods tend to spend more time before they find suitable careers.
Keywords: J21; J24; J62; 330; job mobility; career choice; search; strength of weak ties; social networks